1982
DOI: 10.1002/aja.1001640207
|View full text |Cite
|
Sign up to set email alerts
|

Effects of guanethidine‐induced sympathectomy on morphology of the pre‐ and postclosure lleum of the neonatal rat

Abstract: The disappearance of the characteristic supranuclear vacuole and extensive apical canalicular system from enterocytes of the ileal villi occurs during the third postnatal week in rats. This phenomenon is associated with loss of permeability of these cells to macromolecules and is therefore termed closure. The present study was designed to analyze the influence of neonatal guanethidine (GTN)-induced sympathectomy on the morphology of the pre- and postclosure ileum of the rat. Light and electron microscopy of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1983
1983
2002
2002

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…N E released by the action of the sympathetic nervous system appears to stimulate crypt-cell proliferation in both the small and the large intestine (Tutton and Helme, 1974;Tutton and Barkla, 1977). Neonatal sympathectomy inhibits ileal epithelial-cell proliferation (Klein and McKenzie, 1980), reduces the amplitude of the mitotic circadian rhythm (Klcin, 1981), and retards the morphologic characteristics of ileal closure (McKenzie and Klein, 1982). In the present work, we found that prolonged administration of 6-OHDA resulted in a significant decrease in the labelling index of colon epithelial cells.…”
Section: Tissue Ne Concentrations and Labelling Indicessupporting
confidence: 56%
“…N E released by the action of the sympathetic nervous system appears to stimulate crypt-cell proliferation in both the small and the large intestine (Tutton and Helme, 1974;Tutton and Barkla, 1977). Neonatal sympathectomy inhibits ileal epithelial-cell proliferation (Klein and McKenzie, 1980), reduces the amplitude of the mitotic circadian rhythm (Klcin, 1981), and retards the morphologic characteristics of ileal closure (McKenzie and Klein, 1982). In the present work, we found that prolonged administration of 6-OHDA resulted in a significant decrease in the labelling index of colon epithelial cells.…”
Section: Tissue Ne Concentrations and Labelling Indicessupporting
confidence: 56%
“…In sympathectomized rats this clo sure phenomenon is delayed. Closure is also usually associated with a dramatic increase in the number of goblet cells, which was not evident in the sympathectomized animals (5).…”
Section: Discussionmentioning
confidence: 94%
“…Several studies have documented the effect of guanethidine-induced sympathectomy on intestinal epithelial cell proliferation and morphology in the neonatal rat. Sympathectomy inhibits neonatal ileal cell proliferation and delays the dramatic increase in crypt cell mitotic and labeling indices normally seen at 18 days of age (3)(4)(5). Immature vacuolated cells, permeable to macromolecules, normally disappear from ileal villi by 23 days of age .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The delay in acceleration of mitosis also retards morphological characteristics of closure (197). Immature.…”
Section: Neural and Pharmacological Factorsmentioning
confidence: 99%